The Magic of Magnesium - Dow Chemical Company (1938)
Color print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. The advertisement depicts a sample of magnesium flanked by illustrations of a range of products made from Dowmetal, including airplanes, vacuum cleaners, trains, and machinery. The accompanying text details Dowmetal's lightness and durability relative to other structural metals. This advertisement appeared on the inside cover of the October 1938 edition of Fortune magazine.
Keywords: Dow Chemical Company; Corporations; Chemical industry; Magnesium; Magnesium alloys; Magnesium industry and trade